A Review on JC Virus Infection in Kidney Transplant Recipients - Serena Delbue; Mariano Ferraresso; Luciana Ghio; Camilla Carloni; Silvia Carluccio; Mirco Belingheri; Alberto Edefonti; Pasquale Ferrante (Clinical and Developmental Immunology, 2013)
The polyomavirus (PyV), JC virus (JCV), is a small nonenveloped DNA virus that asymptomatically infects about 80% of healthy adults and establishes latency in the kidney tissue. In case of immunodeficient hosts, JCV can lytically infect the oligodendrocytes, causing a fatal demyelinating disease, known as progressive multifocal leukoencephalopathy (PML). Although the reactivation of another human PyV, BK virus (BKV), is relatively common and its association with the polyomavirus associated nephropathy (PyVAN) following renal transplantation is proven, JCV replication and its impact on graft function and survival are less well studied. Here we describe the biology of JCV and its pathological features and we review the literature regarding the JCV infection analyzed in the setting of transplantations.